P13 The veterans specific activity questionnaire (VSAQ) as a new and effective method of assessing exercise capacity in patients with pulmonary arteriovenous malformations (pavms). (December 2018) - Gawecki, F; Tighe, HC; Perks, J; McKernan, H; Thurairatnam, S; Jackson, JC; Howard, LS; Myers, J; Shovlin, CL
Abstract : Introduction: The presence of pulmonary arteriovenous malformations (PAVMs) is associated with hypoxaemia due to shunting of deoxygenated blood from pulmonary arteries to veins. Evaluation of exercise capacity is problematic using usual dyspnoea scales, since the majority of patients are in Medical Research Council or New York Heart Association Class 1 (normal) pre-treatment, even when oxygen saturation of haemoglobin (SaO2) is <92%. 1 Although cardiopulmonary exercise testing (CPET) can be performed, patient preference and logistics prove limiting in routine clinical practice. Method: Potential methods suitable for PAVM patient exercise ranges were evaluated. In March 2017, a UK-modified version of the Veterans Specific Activity Questionnaire (VSAQ) was developed and incorporated into routine clinic assessments. This validated, simple 13 point self-reported scale permits calculation of the achieved metabolic equivalents (METs) where METS=4.7+0.97(VSAQ)−0.06(age). With ethical approval, the VSAQ results were compared to other routine clinic and research assessments including research protocol CPET. Results: Between 16/03/2017 and 14/05/2018, 115 PAVM patients completed the VSAQ in clinic. All had PAVMs proven by CT scan, with erect SaO2 ranging from 80% to 99.5% (median 96%). Only 27/115 (23.4%) reported needing to stop at activities less energetic than walking briskly at 4 miles per hour. Overall METS ranged from 1.33 to 16.39 kcal/kg/hour (median 8.51, IQR 6.42, 11.92). In univariate analyses, the strongest predictor of METS was the forced expiratory volume in 1 s (FEV1, p=0.001), and not SaO2 (p=0.052). However, once adjusted for FEV1, lower SaO2 were more strongly associated with lower METS (adjusted p-value 0.019). Six patients had also undergone research protocol CPET. In this group, METs was strongly predicted by VO2 peak (adjusted r2 0.78, p=0.013) or anaerobic threshold (adjusted r2 0.65, p=0.032). Conclusions: The VSAQ is a useful and quantifiable measure of exercise capacity that can be readily employed in clinical service. The scale differentials permit sub-categorisation of individuals with normal exercise tolerance, while also evaluating classifying those with more severe dyspnoea. Comparison of VSAQ and CPET results demonstrate it may be a useful substitute to integrate into wider clinical practice. Reference: Santhirapala, et al. PLoS One2014:9(3):e90777. doi:10.1371/journal.pone.0090777